The Penderwicks in spring - Birdsall, Jeanne (New York : Alfred A. Knopf, 2015)
As spring arrives on Gardam Street, there are surprises in store for each Penderwick, from neighbor Nick Geiger's expected return from the war to Batty's new dog-walking business, but her plans to use her profits to surprise her family on her eleventh birthday go astray.--
Sequel to: The Penderwicks at Point Mouette.
"A Junior Library Guild selection"--Jacket flap.
Middle School.
900
Aelerated Reader
Keywords: Families -- Massachusetts -- Juvenile fiction; Surprise -- Juvenile fiction; Birthdays -- Juvenile fiction; Singing -- Juvenile fiction; Single-parent families -- Juvenile fiction; Massachusetts -- Juvenile fiction; Family life -- Massachusetts -- Fiction; Surprise -- Fiction; Moneymaking projects -- Fiction; Birthdays -- Fiction; Singing -- Fiction; Single-parent families -- Fiction; Massachusetts -- Fiction